(untitled) (Baltic Journal of Sport and Health Sciences, 2021)
Laughter yoga is claimed to have similar psychological and physiological effects to exercising. The objectives of the two studies reported here were to examine the visual and practice effects of laughter yoga in women. Study 1 was performed with 13 young women (mean age =21.92 ± SD = 1.66 years) who only experienced laughter yoga visually. Study 2 investigated 25 older women (mean age = 63.83 ± SD = 11.91 years) during an in-situ laughter yoga class. There was no relationship between the humor styles, expectancy, and the magnitude of change in psychological measures, neither in visual nor in the practice experience of laughter yoga. In Study 1, negative affect decreased while feeling states, heart rate, and respiration rate increased because of watching laughter yoga. In Study 2, feeling states, felt arousal, positive affect, and negative affect improved after the class. Even more intriguingly, heart rate also increased, and the basic metabolic rate during the class was comparable to that of light to moderate physical activity. As laughter yoga is characterized by positive psychological and cardiometabolic changes, it could represent a pleasurable, healthy, and secure form of recreation for all, but based on the current results, especially for older women. Keywords: affect, exercise, humor, recreation, social.